Pengaruh Store Atmosphere Dan Promosi Terhadap Keputusan Pembelian Konsumen Pada Zizoba Resto & Coffee Di Kabupaten Tangerang - Anggie Juliaet Supardi; Reza Khairul Hadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the influence of  store atmosphere and promotion on consumer purchase decisions at Zizoba Resto&Coffee in Tangerang Regency. The research method used was descriptive quantitative with the number of samples in the study as many as 95 people. Meanwhile, the primary data collection technique is through a questionnaire which is processed using the SPSS Application System Version 27. The data analysis method uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient, and hypothesis test. The results of this study show that the store atmosphere has a positive and significant effect on consumer purchase decisions with a determination efficiency value of 78.6%, and the hypothesis test obtained a tcal value of > table (18.474 > 1.661 with a significant level of 0.000 < 0.05. Promotion had a positive and significant effect on consumer purchase decisions with a determination coefficient value of 86.6% and the hypothesis test obtained a t-value calculated > tatbel (24.534 > 1.661) or significant 0.000< 0.05. Store atmosphere  and Promotion simultaneously have a positive and significant effect on consumer purchase decisions with the regression equation Y = 0.780 + 0.265X1 + 0.623X2. The value of the determination coefficient was 91.1% while the remaining 8.9% was influenced by other factors that were not conducted by the study. The hypothesis test obtained the value of f calculated > f table or (469.116 > 3.095).